تجلیات الہٰیہ اور انسان کامل: مکتوبات امام ربانی کا تجزیہ: Divine Manifestations and the Perfect Man: An Analysis of Maktubat-e-Imam Rabbani - Usman Haider Saifi (International Research Journal of Arabic and Islamic Studies, 2024)
Human beings are a combination of the world of command and the world of creation, in which all perfections are found. When a person is purified through spiritual refinement and cleansing, their soul is lifted from the darkness of ignorance to the realm of certainty, and they become a complete human being. The spiritual stations and noble ranks that are bestowed upon them are not attainable by anyone else. There are two things within a human being that are not found in the heavenly realm or the macrocosm: one is earthly nature, and the other is divine unity. Human beings are a wonder who has achieved the capacity for vicegerency and has taken on the responsibility of trust. Various manifestations of divine revelation descend upon the perfect human being, including the manifestation of the Essence, which appears in different forms, and the manifestation of divine attributes, which is reflected in the actions of the servant. Similarly, the manifestation of divine light also occurs, in which the veils are lifted from the servant for a short time, and the manifestation of divine unity is witnessed in the mirror of multiplicity, in which the individual ego is completely annihilated. Other manifestations, such as the manifestation of divine presence, the manifestation of divine attributes, and the manifestation of divine essence, also occur, and the human being attains these manifestations, which leads to an increase in their perfections.